Hybrid biofactories: integrating microalgae and engineered microbiomes for enhanced biofuel production in circular carbon systems - Nneoma, Ugwu Chinyere; Chukwudi, Ogenyi Fabian; Nnenna, Ugwu Jovita; Paul-Chima, Ugwu Okechukwu (Frontiers in Energy Research, 2025)
With the growing world demand for sustainable and carbon-neutral energy sources, microalgae have surfaced as a promising source of next-generation biofuels based on their high lipid content, fast growth rate, and their ability to grow on wastewater and carbon dioxide (CO2). Nonetheless, other constraints, including nutritional requirements, threats of contamination, and expensive production processes, make up-scaling challenging. Synthetic biology and microbial ecology have recently allowed engineers to develop, design, and grow synthetic microbiomes, custom microbe communities that can increase microalgal biomass yield, support nutrient reuse, and promote metabolic stability. This mini-review examines the synergistic concept of integrative hybrid biofactories, where microalgae are cultivated concomitantly with designed microbiomes in regulated photobioreactor cultures to realize better biofuel production and environmental sustainability. A particular focus is put on pathway modeling with the help of AI, co-metabolic interactions, and overall system optimization. Putting this discussion into the context of the greater circular carbon economy, the review shows new advances, techno-economic considerations, and prospects on how to scale hybrid systems up to industrial scale.